Synthesis of Polydopamine Functionalized Reduced Graphene Oxide-Palladium Nanocomposite for Laccase Based Biosensor - Da-Wei Li; Lei Luo; Peng-Fei Lv; Qing-Qing Wang; Ke-Yu Lu; An-Fang Wei; Qu-Fu Wei (Bioinorganic Chemistry and Applications)
Graphene based 2D nanomaterials have attracted increasing attention in biosensing application due to the outstanding physicochemical properties of graphene. In this work, palladium nanoparticles (Pd) loaded reduced graphene oxide (rGO) hybrid (rGO-Pd) was synthesized through a facile method. Laccase (Lac) was immobilized on rGO-Pd by utilizing the self-polymerization of dopamine, which generated polydopamine (PDA). The PDA-Lac-rGO-Pd nanocomposites were further modified on electrode surface to construct novel biosensing platform. The obtained electrochemical biosensor was applied in the detection of catechol, achieving excellent analytic results. Under the optimum condition, this biosensor possessed a linear range from 0.1 µM to 263 µM for catechol detection, the sensitivity reached 18.4 µA mM−1, and the detection limit was as low as 0.03 µM. In addition, the biosensor also showed good repeatability, reproducibility, anti-interference, and stability. Moreover, the novel Lac based biosensor was successfully used in the trace detection of catechol existing in real water environment.